Bleeding Risk of Antithrombotic Treatment in Patients on Hemodialysis. Issue 4 (April 2017) - Vázquez, Eduardo; Sánchez-Perales, Carmen; Ortega, Sonia; Vázquez-Sánchez, Teresa; Quesada, Enrique; Salas, Daniel; Fernández-Guerrero, Juan Carlos
Abstract : Background: The risk–benefit of antithrombotic treatment (ATT) has not been established in patients on dialysis. Our objective was to determine the influence of ATT on the risk of hemorrhage in patients on hemodialysis. Methods: We included patients who began dialysis between 2003 and 2007. We determined the rates of fatal bleeding or bleeding leading to hospitalization or transfusion. Results: Two hundred twenty-one patients were included. Over the follow-up period (45.5 ± 34 months), there were 76 hemorrhages in 52 patients. There were 10 fatal bleedings. The annual incidence of patients presenting with hemorrhagia was 6.2%. Bleeding occurred in 5.2% of those being treated with aspirin, 7% with acenocumarol, 12.3% with clopidogrel, 15.2% with aspirin + clopidogrel, 45.9% with anticoagulants + antiplatelets, 49.6% with low-molecular-weight heparin, and 3.9% without ATT. On multivariate analysis, masculine gender [hazard ratio (HR): 2.421; 95% confidence interval (CI), 1.261–4.650; P = 0.003], treatment with dicumarins (HR: 2.406; 95% CI, 1.013–5.718; P = 0.047), treatment with clopidogrel (HR: 2.697; 95% CI, 1.440–5.051; P = 0.002), and treatment with low-molecular-weight heparin (HR: 21.463; 95% CI, 9.067–50.806; P = 0.001) were independent predictors of bleeding. Conclusions: ATT increases the risk of bleeding in patients on hemodialysis. The incidence of hemorrhage varies with the type of antithrombotics used.